Contracepção e fatores associados ao não uso de métodos contraceptivos pelas mulheres brasileiras após o parto: comparação entre os inquéritos nacionais de 2006 e 2013 - Bárbara Barrozo Siqueira (2020)
Introduction: Adequate spacing between pregnancies is part of the Family Planning (FP) actions because a minimum interval is necessary to ensure the biopsychosocial recovery of women in the postpartum period. However, there are gaps in knowledge regarding the neglected and vulnerable subgroups of FP actions in Brazil, with emphasis on studies with national representativeness for postpartum women and all women, regardless of their marital status. Objective: To assess changes in the prevalence of use and in the contraceptive pattern of Brazilian women up to two years after pregnancy, between 2006 and 2013, and the sociodemographic factors associated with the non-use of contraceptive methods (CM). Methods: This is a cross-sectional, descriptive and analytical study which used secondary data from the surveys: Pesquisa Nacional de Demografia e Saúde da Mulher e da Criança (2006) and Pesquisa Nacional de Saúde (2013). We studied Brazilian women with up to 2 years postpartum, of reproductive age, sexually active, non-pregnant and menstruating, and compared them with all the other women. We estimated the prevalence of use, contraception pattern of contraception and ranking of modern methods. Prevalence of non-use of CM was assessed according to sociodemographic characteristics and access to information regarding the FP,using logistic regression to estimate the unadjusted and adjusted Odds Ratios. Percentual change in indicators between the years was evaluated by calculating the difference between estimates. We considered the complex sample design of the surveys to obtain population estimates. Results: About 85% of Brazilian women used CM, remaining stable in 2006 and 2013, with a high prevalence of modern methods use. An increase in the use of CM was observed among those with up to six months postpartum (71.0% to 89.0%). Pills and condoms accounted for about 60% of modern methods used in the postpartum period in both surveys. There was an increase in dual protection (2.9% to 10.1%) and contraceptive insecurity (1.6% to 5.7%) and a reduction in sterilization (16.2% to 13.4%) and traditional methods (2.1% to 1.4%). Women living in the North and Northeast regions and not living with a partner had 3 times the chance of not using CM in 2006 and 2013. Conclusion: Even with the maintenance of a high prevalence of use of CM and with the increase in contraception among women with up to six months postpartum, regional inequalities in access to CM and low prevalence of the use of other methods made available by the Unified Health System (SUS) persist, pointing out the maintenance of the insufficient care, failures in the means to regulate fertility and that public policies still hinder to guarantee the sexual and reproductive rights of the most vulnerable population. Therefore, it is necessary to expand the reach of the CM and qualify the offered by SUS, through the qualification and training of professionals, especially nurses, to increase the better offer of CM in the postpartum period.